The Effect of Societal bilingualism (Cypriot Dialect) and Greek language as a Secondary/Foreign Language in the Production of Oral and Written Communication - Ζαννεττίδου-Πουγεράση Δέσποινα (Education Sciences, 2020)
This paper is researching how social bilingualism (Greek Language and Cypriot Dialect) influence the construction of speech/writing in classes of mixed ability and linguistic diversity in Elementary Education. Basically, it has been investigated (MANOVA) whether the individual characteristics and demographics of 3rd grade children (gender, language at home and mother tongue: AM) affect the linguistic level (Athena Test: Completion of sentences, Linguistic Analogies, vocabulary: EM) and the usage of dialect components (EM) in the written expression. Through qualitative research, the speech/writing was commented on Grammar/Syntax, Phonology, Spelling, Dictionary, Reasoning before and after teaching (subject: Free Time). Through a questionnaire we see the sociolinguistic perceptions, views, behavioral attitude of teachers on the teaching of Greek as a mother/first tongue as well as foreign/secondary in the context of linguistic formation in mixed ability and heterogeneous linguistic classes.